Epidemiology of pre-existing multimorbidity in pregnant women in the UK in 2018: a cross-sectional study. (November 2021) - Lee, Siang Ing; Azcoaga-Lorenzo, Amaya; Agrawal, Utkarsh; Kennedy, Jonathan I; Fagbamigbe, Adeniyi Francis; Hope, Holly; Subramanian, Anuradhaa; Anand, Astha; Taylor, Beck; Nelson-Piercy, Catherine; Damase-Michel, Christine; Yau, Christopher; et al.
Abstract: Background: Although maternal death is rare in the UK, 90% (510 of 566 deaths) of women who died during or within a year after pregnancy in 2016–18 had multiple health and social problems (MBRRACE-UK). This study aims to estimate the prevalence of pre-existing multimorbidity in pregnant women in the UK. Methods: Pregnant women aged 15–49 years with a conception date between Jan 1 and Dec 31, 2018, were included in this cross-sectional study, using routine health-care datasets: Clinical Practice Research Datalink (CPRD) GOLD (UK, n=37 641), Secure Anonymised Information Linkage (SAIL) databank (Wales, n=27 782), and Scottish Morbidity Records (SMR, secondary care) with linked community prescribing data (Tayside and Fife, n=6099). We defined pre-existing multimorbidity (two or more morbidities) preconception from 79 long-term physical and mental health conditions. This definition was identified from the literature and prioritised by the multidisciplinary research advisory group, including patient representatives. The association of women's characteristics preconception with multimorbidity was examined with logistic regression. The University of St Andrews School of Medicine Ethics Committee approved this project. Participant consent was not required as the data used are anonymised. Interpretation: Prevalence of multimorbidity was 44·2% (95% CI 43·7–44·7) in CPRD, 46·2% (45·6–46·8) in SAIL, and 19·8% (18·8–20·8) in SMR. Mental health conditions were highly prevalent and involved 70% of multimorbidity (CPRD: prevalence of multimorbidity with one or more mental health conditions 31·3% [30·8–31·8]). Pregnant women with conditions that were leading causes of maternal deaths had a high prevalence of multimorbidity (CPRD: 745 [2·0%] of 37 641 women had cardiovascular disease, of whom 597 [80·1%] had multimorbidity). Higher maternal age (CPRD: adjusted odds ratio 1·81 [95% CI 1·04–3·17] for 45–49 years vs 15–19 years), gravidity (1·68 [1·50–1·89] for ≥5 vs 1), BMI (1·59 [1·44–1·76], for ≥30 vs 18·5–24·9) and smoking (1·61 [1·46–1·77] for smoker vs non-smoker) were significantly associated with multimorbidity. Ethnicity and deprivation were not significantly associated with multimorbidity. Interpretation: A significant proportion of women enter pregnancy with pre-existing multimorbidity, especially mental health conditions. Pregnant women with multimorbidity were more likely to smoke and have a raised BMI and support may be required to address this. There may be health-care access inequalities for some health conditions, especially mental health conditions in pregnant women from deprived or ethnic minority groups. Secondary care and linked community prescription dataset captured severe conditions and might underestimate the prevalence of multimorbidity. Urgent research is needed to quantify the consequences of maternal multimorbidity for mother and child. Funding: This work was supported by the joint UKRI-NIHR Strategic Priorities Fund consolidator grant (grant number MR/V005243/1). BT was funded by the National Institute for Health Research (NIHR) West Midlands Applied Research Collaboration. AA and SIL were funded as NIHR Academic Clinical Fellows. The views expressed are those of the author and not necessarily those of the funders, the NIHR or the UK Department of Health and Social Care.